The effect of banking services quality standards on customer’s satisfaction from the point of view of customers of the National Bank of Algeria in Djelfa - Seddiki, Naas; Saida, Oubah; Redouane, Enssad (Dirassat Journal Economic Issue, 2021)
The study aimed to identify the characteristics and dimensions of the quality of banking service and showing its role as a means to enhance and achieve customer’s satisfaction, as we used in this study the descriptive and analytical method, to achieve the aim of the study, a questionnaire form was prepared for this purpose and it was distributed to a sample of 155 clients from the national bank of algeria in djelfa. to address the study hypotheses, spss statistical analysis program was used. The study found an impact of the quality of banking services on customer’s satisfaction. the study concluded with a set of recommendations. the most important of which are:the necessity of adopting modern concepts of marketing by enhancing and supporting quality elements of banking services in line with the requirements of customers.